Možnosti primerjave skladnosti meritev med skupinami - Vidmar, Gaj (Informatica Medica Slovenica, 2010)
Rehabilitation of persons after lower limb amputation includes provision of a prosthesis. Before that, it should be established how much strain would walking with a prosthesis cause to the patient. For this purpose, we performed 6-minute walk test and exercise testing using hand-wheel ergometer in 101 patients after transfemoral amputation. We wanted to establish at which level of exercise power is the vascular response, as measured by oxygen uptake, closest to the response during walk test. We used various statistical methods of agreement analysis. The article reviews the numerous available approaches to the analysis of agreement for numeric variables with an emphasison comparing agreement between groups.
Keywords: amputees; amputiranci; hoja; lower limb; rehabilitacija; rehabilitation; spodnji ud; walk